2023
DOI: 10.3390/ijms24044141
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Mechanical Properties of Fast and Slow Skeletal Muscle after 7 and 21 Days of Restricted Activity in Rats

Abstract: Disuse muscle atrophy is usually accompanied by changes in skeletal muscle structure, signaling, and contractile potential. Different models of muscle unloading can provide valuable information, but the protocols of experiments with complete immobilization are not physiologically representative of a sedentary lifestyle, which is highly prevalent among humans now. In the current study, we investigated the potential effects of restricted activity on the mechanical characteristics of rat postural (soleus) and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…As susceptibility to muscle atrophy has been shown to differ greatly among different subjects 32,46 and different muscles 25,26 , this might explain partially contrasting reports from different human cohorts of limited size and heterogeneous age. These data suggest that the decrease of muscle CSA caused by unloading can be accompanied by loss of mitochondria and oxidative capacity at Earth gravity, particularly at longer time points than ten days or in harsher unloading conditions, such as dry immersion 47 . However, data on short space flight in humans seem to indicate that the effects on mitochondrial downregulation may be much stronger and faster in the space environment 35 .…”
mentioning
confidence: 79%
“…As susceptibility to muscle atrophy has been shown to differ greatly among different subjects 32,46 and different muscles 25,26 , this might explain partially contrasting reports from different human cohorts of limited size and heterogeneous age. These data suggest that the decrease of muscle CSA caused by unloading can be accompanied by loss of mitochondria and oxidative capacity at Earth gravity, particularly at longer time points than ten days or in harsher unloading conditions, such as dry immersion 47 . However, data on short space flight in humans seem to indicate that the effects on mitochondrial downregulation may be much stronger and faster in the space environment 35 .…”
mentioning
confidence: 79%
“…It has been shown that mechanical tension load have an important effect on myo ber type transformation [20][21][22] . Fajardo et al overloaded the plantar exor muscles and unloaded the dorsal extensor muscles in mice and found that tension load could affect the transformation of myo ber types.…”
Section: Discussionmentioning
confidence: 99%
“…However, to better identify the change in the mechanical behavior of the muscle, samples transversely cut could also be used (Simon and Zidi 2022), although this would be more difficult due to the small size of the immobilized muscle. In addition, muscle fibers could also be studied, as it has been shown that immobilization can lead to a transition from type I to type II fibers, specifically for slow MHC muscles (Booth and Kelso 1973b;Udaka et al 2008;Tyganov et al 2023) but not for fast MHC muscle (Tyganov et al 2023). A comparison with other immobilized skeletal muscles could confirm this.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%